2010
DOI: 10.1021/bi901745f
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-Induced Structuralization and Glass Formation of Group 3 Late Embryogenesis Abundant Protein Model Peptides

Abstract: Anhydrobiotic (i.e., life without water) organisms are known to produce group 3 late embryogenesis abundant (G3LEA) proteins during adaptation to severely water-deficient conditions. Their primary amino acid sequences are composed largely of loosely conserved 11-mer repeat units. However, little information has been obtained for the structural and functional roles of these repeat units. In this study, we first explore the consensus sequences of the 11-mer repeat units for several native G3LEA proteins originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 51 publications
6
113
0
Order By: Relevance
“…%, again matching experimental results with CD and FTIR (e.g., (59,60,63,64)). In the dehydrated state the structure is primarily α-helix.…”
Section: Increase In Secondary Structure During Dryingsupporting
confidence: 82%
See 1 more Smart Citation
“…%, again matching experimental results with CD and FTIR (e.g., (59,60,63,64)). In the dehydrated state the structure is primarily α-helix.…”
Section: Increase In Secondary Structure During Dryingsupporting
confidence: 82%
“…Interestingly, slow drying reversibly led to both α-helical and intermolecular extended β-sheet structures, which suggested the final protein conformation was not predetermined. Increase in secondary structure during drying also has been reported for LEA proteins from groups 1 and group 2 (dehydrins) (61,62), and for other group 3 proteins and peptides (63,64).…”
Section: Increase In Secondary Structure During Dryingmentioning
confidence: 55%
“…The most remarkable result is the striking integrity of 93.6 ± 4.6% (n = 9) measured for HepG2-AfrLEA3m cells in the absence of trehalose. Consistent with this finding, evidence indicates that model synthetic peptides composed of several tandem motifs of group 3 LEA proteins (22-to 44-aa residues) vitrify at a high T g , which suggests that dried LEA proteins themselves may vitrify and act in this way as excellent protectants against desiccation damage (45). It is appropriate to emphasize that although AfrLEA3m is indeed mitochondrialtargeted, synthesis occurs in the cytosol, and importation into mitochondria is time-dependent (26), and thus presumably some fraction of the protein is continuously present in the cytoplasm.…”
supporting
confidence: 55%
“…Thus, both cellular treatments containing LEA-sugar mixtures display ∼98% membrane integrity after severe desiccation. In vitro studies have shown that mixing LEA-like peptides into trehalose solutions stabilizes the vitrified sugar glasses on drying, as judged by upward shifts in T g (45). Growth studies conducted across ensuing days after rehydration of dried cells revealed the greatest proliferation for those cells containing AfrLEA3m plus trehalose compared with all other treatment groups (Fig.…”
mentioning
confidence: 93%
“…This is a characteristic of highly hydrophilic proteins, such as LEA proteins and this suggests that PvLEA proteins may protect other proteins from aggregation and denaturation during anhydrobiosis in P. vanderplanki. Recently, a study on group 3 LEA model peptides, obtained from P. vanderplanki and other anhydrobiotes, showed that LEA proteins participate actively in the vitrification process (49), not only by forming glass by themselves but also by stabilizing the trehalose glassy matrix (see below). This mechanism for combating dehydration stress is probably common to animals, plants, and microorganisms, because LEA proteins are widespread throughout many phyla, although limited to desiccation tolerant organisms.…”
Section: Late Embryogenesis Abundant Proteinsmentioning
confidence: 99%